Let's call the cost of the pants "p", the cost of the shirt "s", and the cost of the coat "c".
From the first sentence, we know that:
p + s + c = (1)
From the second sentence, we know that:
p + c = 244.50 (2)
And from the third sentence, we know that:
c = 5s (3)
We can use equation (2) to solve for "p":
p = 244.50 - c
Then we can substitute that into equation (1) and also substitute equation (3) for "c":
(244.50 - c) + s + 5s = 100.90
Simplifying:
6s = 344.60
s = 57.43
Now we can use equation (3) to find "c":
c = 5s = 5(57.43) = 287.15
So, Mr. Zubir paid $287.15 for the coat.
Mr Zubir bought a pair of pants, a shirt and a coat. The pants
and the shirt cost $100.90. The pants and the coat cost $244.50.
The coat cost 5 times as much as the shirt. How much did
Mr Zubir pay for the coat?
2 answers
The coat cost more than the pants and the coat together?
Redoing
p + s = 100.90
p + c = 244.50
----------------------- subtract
s - c = - 143.60
and
c = 5 s
so
s - 5 s = -143.60
-4 s = -143.60
s = 35.90 for a shirt
now
c = 5 s = 179.50
Redoing
p + s = 100.90
p + c = 244.50
----------------------- subtract
s - c = - 143.60
and
c = 5 s
so
s - 5 s = -143.60
-4 s = -143.60
s = 35.90 for a shirt
now
c = 5 s = 179.50